Test-Retest Reliability of Low-Cost Posturography for Assessing Postural Stability Control Performance during Standing - Sumet Heamawatanachai; Witawit Wiriyasakunphan; Kanokwan Srisupornkornkool; Chaiyong Jorrakate (Journal of Aging Research)
Postural stability control performance assessment is necessary in providing important information for individuals who are at risk of falling or who have balance impairment. Instrumented assessment is suggested as a valid and reliable test, but the cost and the difficulty of setup are significant limitations. The aim of this cross-sectional (test-retest reliability) study was to develop and determine the reliability of a low-cost posturography for assessing postural stability control performance during standing. The low-cost posturography was developed with four load cells and an acrylic platform. The center of pressure (COP) displacement and velocity were analyzed using written software. Test-retest reliability was performed with six different standing postural stability tests in twenty healthy volunteers on two different days. Intraclass correlation coefficient (ICC), standard error of measurement (SEM), coefficient of variation (CV), and Bland–Altman plot and limits of agreements (LOA) were used for analyses. The low-cost posturography was accurate (ICC = 0.99, p<0.001; SEM = 0.003 cm) when compared to the true with calculated X and Y coordinates, with a moderate to excellent test-retest reliability for both COP displacement (ICCs ranged 0.62–0.91, p<0.05; SEMs ranged 17.92–25.77%) and COP velocity (ICCs ranged 0.62–0.91, p<0.05; SEMs ranged 18.09–27.69%) in all standing postural stability tests. Bland–Altman plots and LOAs suggested good agreement of tested parameters from the developed low-cost posturography between different days. In conclusion, the developed low-cost posturography had adequate reliability for assessing COP displacement and velocity during standing postural control stability performance tests.